Sustainable food crop production in karst area of Parigi, Pangandaran, West Java: preliminary study - Reginawanti Hindersah; Nia Kurniati; Dadang Epi Sukarsa; Rustam Rustam; Sondi Kuswaryan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
Karst formations in Selasari and Parakanmanggu Village of Parigi District, Pangandaran Regency, West Java includes dolines, subterranean stream, springs, and karst hills are useful for agriculture. The purpose of this study was to 1) identifiy the used of karst area for rice cultivation and local trees in karst area; 2) evaluate the benefit of rice cultivation and local tree for local communities and 3) asses the legal aspect for supporting food crop production. The study was done using qualitative-descriptive method with the primary data obtained from field observations, soil analysis, local tree identification, and interviews. Secondary data was obtained from the Regional Government and the National Geological Agency. The results showed that rice cultivation has been carried out in suitable soil by using simple and rainfed irrigation. Local fruit, herbs, timber and shade-ornamental tree grow naturally on the karst area. Tree logging without significant revegetation caused water supply shortage so that farmers only grow rice once a year. Athough the rice productivity of both villages is lower than average rice productivity of Pangandaran Regency, rice is important to support local inhabitant’s consumption and family income. Land Use Plan year 2018 regulates the general provisions on zoning regulations for agriculture in susceptible area but the regulation does not mention the karst areas. This study suggested that tree conservation is needed to maintain the existence of rice fields. Land use planning for agriculture in the region must be based on integrated considerations of rice cultivation and local tree conservation.